Women Empowerment and Their Decision-Making Supremacy : a Literature Review Approach - Nivedita Agnihotri (Research Synergy Foundation, 2021)
Women are an integral part of our society; they have to play diverse role to contribute in economy. Harmonious growth and development of any nation is possible only when women are equally participating in the development process with men. However, in most of the developing countries, the socio-economic status of women is very low. In this paper, we provide a literature review to compared the working and non-working women in household decision-making, using secondary data. We find out that woman’s decisions making power is clearly related to the context in which she lives. It is observed that decisions made by working and educated women get greater substance than the decisions taken by non-working and less educated women. However, Urban and employed women have greater awareness about their rights than rural and illiterate women. In the previous studies, most women are deprived of economic and educational roles opportunities and decision-making. Decision-making of women is controversially as low as the roles and responsibilities of each sector while their male counterparts have relatively high decision-making. Furthermore, we find out that electronic media is also playing an important role behind the women empowerment, since it provides information to women about the world issues, which encourages their self-confidence and motivates them to participate in household matters.